Fossil woods from the Eocene of Corcovado, Argentinean Patagonia: geological setting and conifer diversity - Pujana, Roberto Roman; Aramendía, Inés; García Massini, Juan Leandro; Noetinger, Maria Sol (IAWA Journal)
Eocene paleofloras of Patagonia are diverse and increasingly known. A new assemblage of fossil wood has been recovered from Eocene sediments in Corcovado, western Argentinean Patagonia. The lithological succession (formerly Arroyo Lyn Formation sensu Pesce 1979) is correlated with the Huitrera Formation. The specimens were mostly found embedded in sandstones and conglomerates. One-third of the assemblage are conifers and studied herein. We found four taxonomic types: Agathoxylon cf. antarcticum (Araucariaceae), Phyllocladoxylon antarcticum (Podocarpaceae), Podocarpoxylon dusenii (Podocarpaceae), and Cupressinoxylon hallei (Cupressaceae or Podocarpaceae). The presence of four taxonomic units among only 7 specimens suggests a significant conifer species richness in the assemblage. Araucariaceae and dominant Podocarpaceae are usually found in previously described conifer wood assemblages from the Eocene of Patagonia andAntarctica. The diversity of the conifer assemblage in Corcovado is very similar to that found at Laguna del Hunco (these two localities are 170 km distant), also from the Huitrera Formation. This is consistent with the proposal that the bearing sediments of both localities are from the same stratigraphic unit. Fil: Pujana, Roberto Roman. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Aramendía, Inés. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Estudios Andinos "Don Pablo Groeber". Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Estudios Andinos "Don Pablo Groeber"; Argentina Fil: García Massini, Juan Leandro. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Regional de Investigaciones Científicas y Transferencia Tecnológica de La Rioja. - Universidad Nacional de La Rioja. Centro Regional de Investigaciones ...